Case Report: Stroke-like migraine attacks after radiation therapy syndrome: a rare complication 26 years after cranial radiotherapy - Duranikova, Olga; Straka, Igor; Melichercik, Lubomir; Marcek, Peter; Gmitterova, Karin; Valkovic, Peter (Frontiers in Oncology, 2023)
Stroke-like migraine attacks after radiation therapy (SMART) syndrome is a rare delayed complication of cranial radiotherapy, that may present decades after brain irradiation. Here we present a case of 41-year old patient with a history of grade 3 oligodendroglioma, epilepsy and migraine, 26 years after brain radiation therapy, who was admitted with right hemicranial headache, nausea, left homonymous hemianopsia, weakness of the left arm and left-sided hemihypesthesia.After considering alternate diagnoses, we ultimately diagnosed SMART syndrome. Despite its rare occurrence and unknown pathophysiology, there are more case reports of SMART syndrome reported due to advancements in oncology treatment and increasing patients' survival rates.Therefore, diagnosis of SMART syndrome should always be considered in patients with a history of cranial radiation presenting with focal neurologic deficits and migraine, especially with a change in pattern of their usual migraine attack.